2009
DOI: 10.1590/s0036-36342009000200009
|View full text |Cite
|
Sign up to set email alerts
|

AgNOR polymorphism association with squamous intraepithelial lesions and invasive carcinoma with HPV infection

Abstract: AgNOR polymorphism association with squamous intraepithelial lesions and invasive carcinoma with HPV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…This can be useful as a prognosis for the progression of squamous cell carcinoma. The present study which was done on precancerous and cancerous lesions of the cervix, similarly showed that the AgNOR was valuable as a cellular activity marker and as well as a marker of malignancy [11].…”
supporting
confidence: 61%
“…This can be useful as a prognosis for the progression of squamous cell carcinoma. The present study which was done on precancerous and cancerous lesions of the cervix, similarly showed that the AgNOR was valuable as a cellular activity marker and as well as a marker of malignancy [11].…”
supporting
confidence: 61%
“…In our study, no statistical difference between the variation of AgNOR dots size and dispersion between dysplastic versus the SCC group was found. Alarcón‐Romero Ldel et al 21 . evaluated the relationships between AgNOR polymorphisms, squamous intraepithelial lesions and SCC with human papillomavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of staining was classified according to the polymorphism of AgNOR dots; typical (spherical) and atypical (large, kidney‐shaped and clustered). They found that AgNOR polymorphism rose progressively according to the grade of histological lesions and therefore this marker was useful in the prognosis of SCC 21 …”
Section: Discussionmentioning
confidence: 99%
“…They have found the pleomorphism of AgNOR increasing with progression of histopathological lesions, and the highest number was seen in squamous cell carcinoma [810]. The study assumes importance with the report of Alarcón-Romero et al that a significant difference was found with different types of AgNOR dots with infection of high-risk HPV types [10].…”
Section: Discussionmentioning
confidence: 83%
“…This has become imperative in view of the findings of Alarcón-Romero et al that the pleomorphic dots are related to the HPV infection [10]. In the present study, AgNOR dots, both pleomorphic and single, have been counted in cervical smears under different pathological conditions of the uterine cervix, and the data has been analysed to discover the relation between the quantity of the two types of dots with the progression of the disease.…”
Section: Introductionmentioning
confidence: 93%